Upgrade of a variable temperature scanning tunneling microscope for nanometer-scale spectromicroscopy - B. Cirera; A. Sáez-Coronado; D. Arribas; J. Méndez; A. Sagwal; R. de Campos Ferreira; M. Švec; P. Merino (MethodsX)
Tip-enhanced Raman spectroscopy (TERS), tip-enhanced photoluminescence (TEPL), and scanning tunneling microscope-induced luminescence (STML) combine the high spatial resolution of probe microscopies with the spectroscopic capabilities of optical techniques. Here, we describe the upgrade of an ultrahigh vacuum (UHV) variable-temperature scanning probe microscope (VT-SPM) to perform tip-enhanced spectromicroscopy experiments at cryogenic temperatures. The home-made design includes a portable focusing lens (NA=0.45) that allows the simultaneous collection and injection of light from the tip-sample junction while assuring easy tip and sample transfers. We demonstrate the capabilities of our upgrade to resolve electroluminescence (EL), Raman, and TERS spectra using plasmonically active probes (Ag and Au tips) on various surfaces. We are able to observe the vibrational levels of C60 deposited on Ag(111) with a lateral resolution of ∼2 nanometers. Moreover, we use the tunability of the gap plasmon distribution to observe intense anti-Stokes signals of C60, highlighting the spectral sensitivity of the system. This upgrade opens new possibilities for studying surface chemistry, catalysis, and molecular electronics at state-of-the-art spatial and spectral resolutions using accessible SPM systems. • Portable lens holder • In-situ adjustable position • Nanometer-scale vibrational spectroscopy